THE INFLUENCE OF COMPETENCE AND JOB CHARACTERISTICS ON PERFORMANCE WITH MOTIVATION AS MEDIATING VARIABLE AT REGIONAL FINANCE AGENCY OF TEGAL CITY - Rijanti, Tristiana; Priyono, Bambang Suko; Nugroho, Heri Prasetiyo (Proceeding Fakultas Ekonomi, 2017)
This study examined the effect of Competence and job characteristics on Performance with motivation as a mediating variable. The population in this study is 105 employees of Regional Finance Agency of Tegal City. The sampling technique is used census. The technique of collecting data used questionnaires with likert scale. Using SPSS version 19.0 the data is analyzed with instrument test, regression analysis for hypothesis test and mediating test. The result shown (1) Competence  positively significantly  influences motivation; (2) Job characteristics  positively significantly  influences motivation; (3) Competence positively significantly  influences performance;(4) Job characteristics  positively significantly  influences performance; (5)Motivation is not proven influences on performance; (6)Motivation is not proven as mediating variables  the influence of both Competence and Job characteristics on Performance. Keywords : Competence, Job Characteristics, Motivation, and Performance